Effects of β-diketone antibiotic mixtures on behavior of zebrafish (Danio rerio). (February 2016) - Wang, Xuedong; Zheng, Yuansi; Zhang, Yuna; Li, Jieyi; Zhang, Hongqin; Wang, Huili
Abstract: To date, few data are available on neurotoxicity of β-diketone antibiotics (DKAs) from the perspective of animal behavior. Herein, the effects of long-term DKAs exposure on zebrafish ( Danio rerio ) behavior were assessed for locomotor activity, anxiety, social interaction and their related molecular mechanisms. DKAs exposure to zebrafish consisted of six DKA species, including ofloxacin, ciprofloxacin, enrofloxacin, doxycycline, chlortetracycline and oxytetracycline, with equal weight concentration and equal volume. DKAs at 6.25 mg/L significantly increased the time spent in the upper portion of the test tank (+40%) and the number of line crossings (±42%), indicating occurrence of anxiolytic behavior. For conditioned place preference test, long-term DKAs exposure at 6.25 mg/L increased the number of motionless positions in the non-preferred white side (+31%), number of transitions to the white side (+221%) and time spent in the white side (+35%) in relation to the control. DKAs at 6.25 mg/L significantly increased zebrafish shoaling behavior (+38%) resulting from an anxiety-like state, but 25 mg/L DKAs exposure decreased zebrafish social cohesion (−41%) possibly due to an autism-like state. With increasing DKAs-exposure concentration, the signal intensity of 1 O2 gradually decreased, leading to insufficient energy supply and movement functional disorders. Based on GO functional annotation and metabolic pathway analysis, 11 genes closely associated with locomotor behavior were identified. Using qRT-PCR, we confirmed that DKAs exposure led to changes in the transcriptional levels of 11 locomotor-related genes. These results suggest that behavior is a potential strategy for evaluating mechanisms underlying the neurochemical basis triggered by stress in zebrafish. Highlights: DKAs increased time spent in upper portion of test tank and number of line crossings. DKAs at 6.25 mg/L increased zebrafish shoaling behavior from an anxiety-like state. With increasing DKA concentration, the signal intensity of 1 O2 gradually decreased. DKAs led to severe tissue damage of zebrafish including pyknosis of nucleous, etc. DKAs exposure led to changes in transcriptional levels of 11 locomotor-related genes.